THE CONTEMPORARY SERBIAN PROSE AND POSTCOLONIAL DI-LEMMAS - Perišić, Igor (Porównania, 2015)
This paper presents a short panorama of Serbian literature of the last decade of the previous and the first decade of this century from the perspective of postcolonial theories. „The animal“ paradigm will serve as the formal construct, used in the present text for deliberations about forms of coexisting in con-temporary Serbian literature of that which is personal, private, native, „domesticated“, which is associated with the demystification of great nationalist and capitalist narrative. The findings of theoreticians of postcolonialism are used as the methodological tool for the presentation of the strategy applied in employed reflection over global dilemmas of poetics and politics.